The nature of job satisfaction and the effect of marital status on job satisfaction in organisations in ghana - Francis Duah; Kyeremeh Kofi (Journal of Management and Science, 2022)
The paper investigates the satisfaction level of employees in organisations concerning job satisfaction variables. The sample size for the study consists of 139 employees of public and private institutions in Ghana. The results indicate a high level of satisfaction of the variables examined, with the three most satisfying variables been respect for workers, devotion to work, and learning from colleagues respectively. Also, marital status differences exist in job satisfaction of the respondent's satisfaction of the variables.The research influences the future performance of an organisation by paying attention to job satisfaction variables within the institutions to positively influence the motivation of workers to improve productivity. Future studies should examine the effect of demographic factors on job satisfaction variables and also the effect of emotional intelligence on job satisfaction variables. Also,the association between employee’s motivation and job satisfaction variables as well as job performance and job satisfaction variables should be examined. Causal studies in these areas are worth embarking on.